Effects of elevated nutrient supply on litter decomposition are robust to impacts of mammalian herbivores across diverse grasslands - Adrienne B. Keller; Elizabeth T. Borer; Christopher R. Buyarski; Elsa E. Cleland; Allison Gill; Andrew S. MacDougall; Joslin L. Moore; John W. Morgan; Rebecca L. McCulley; Anita C. Risch; Eric W. Seabloom; Justin Wright; et al. (Oecologia, 2025)
Litter decomposition is one of the largest carbon (C) fluxes in terrestrial ecosystems and links aboveground biomass to soil C pools. In grasslands, decomposition drivers have received substantial attention but the role of grassland herbivores in influencing decay rates is often ignored despite their potentially large effects on standing biomass and nutrient cycling. Recent work has demonstrated that nutrient addition increases early-stage decay and suppresses late-stage decay. Mammalian herbivores can mediate the effects of nutrient supply on biomass, suggesting herbivores may alter the effects of nutrients on decomposition, though this is largely unknown. We examined how herbivory mediates the effects of nutrient supply on long-term decomposition across 19 grassland sites of the Nutrient Network distributed experiment. At each site, a full-factorial experiment of combined nitrogen (N), phosphorus (P), and micronutrient (K) enrichment (‘control’ or ‘ + NPK’) and mammalian herbivore (> ~ 50 g) exclusion (‘unfenced’ or ‘fenced’) was carried out in a randomized block design. We hypothesized that nutrient effects on litter decomposition would be strongest where herbivores caused the greatest reductions in aboveground plant biomass (i.e., at sites with more intense herbivory). After accounting for wide variation in decomposition rates across sites, we found that, within sites, elevated nutrients increased early-stage decay and suppressed late-stage decay. In contrast, neither herbivore exclusion (i.e., fencing) nor site level changes in aboveground biomass due to herbivory altered the nutrient effects on decomposition rates. Across grasslands, our results indicate that elevated nutrient supply modifies litter decomposition rates independent of herbivore impacts.